216k views
4 votes
PLEASE HELP ME THIS IS MY 2ND TIME ASKING

PLEASE HELP ME THIS IS MY 2ND TIME ASKING-example-1
User Sparkmix
by
4.5k points

2 Answers

6 votes

Answer:

yes

Explanation:

0.4(k+3) = 0.4k+1.2

expand 0.4(k+3)

0.4 x k = 0.4k

0.4 x 3 = 1.2

so...

0.4k + 1.2

User KrishPrabakar
by
6.7k points
0 votes

Answer: B, Equivalent 0.4(k+3) = 0.4k +1.2

Explanation:

when you distribute the 0.4 across k and 3, you multiply 0.4 by k and 3, getting you 0.4k+1.2 which is equivalent.

User Jithesh
by
6.0k points